Rules - Lord, Cynthia (New York Scholastic, 2008)
Frustrated at life with an autistic brother, twelve-year-old Catherine longs for a normal existence but her world is further complicated by a friendship with a young paraplegic.
M
b
b
Keywords: Autism -- Fiction; Siblings -- Fiction; People with disabilities -- Fiction